Design and demonstration of direct UV-written small angle X couplers in silica-on-silicon for broadband operation - Adikan, Faisal Rafiq Mahamd; Gawith, Corin B.E.; Smith, Peter G.R.; Sparrow, Ian J.G.; Emmerson, Gregory D.; Riziotis, Christos; Ahmad, Harith (Optical Society of America, 2006)
Experimental demonstration of small angle (0.8 degrees-5 degrees) direct UV-written X couplers in silica-on-silicon is presented. Maximum and minimum coupling ratios of 95 (+/- 0.8) and 1.9 (+/- 1), respectively, were recorded. The structures also display very low polarization and wavelength dependence. A typical excess loss of 1.0 dB (+/- 0.5 dB) was recorded. Device modeling using the beam propagation method and an analytical model showed good agreement with experimental results over a broad crossing angle and wavelength range. (C) 2006 Optical Society of America.